IMPROVEMENT OF MATHEMATIC LITERACY FOR FIRST HIGH SCHOOL STUDENTS THROUGH PROBLEM-BASED LEARNING ASSISTED IN ISLAMIC INTEGRATED GEOMETRY STUDENT WORKSHEETS - Masamah, Ulfa; Zain, Nurmalia Khoirunisa; Salsabila, Anisah; Maulidani, Muhammad (Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study aims to analyze the improvement of students' mathematical literacy through problem-based learning with the help of Islamic integrated geometry Student Activity Sheets. This study is a quasi-experimental study with a non-equivalent control group design. The variable of this research is a problem-based learning model assisted by student activity sheets as the independent variable and mathematical literacy as the dependent variable. The population of this study were students of MTs Surya Buana Malang City with the sample being class IX students. With class IX A as the experimental class and class IX B as the control class. The research instrument used in this study was a description test. The data analysis technique used independent sample t-test. The results of the study concluded that the increase in mathematical literacy of students who received problem-based learning assisted by Islamic integrated geometry student activity sheets was significantly better than students who received conventional learning.